INVESTIGATION OF PARAMETERS OF HYDROMONITOR JET OF A BIT - Moisyshyn, V. M.; Biletsky, Ya. S.; Seniushkovych, M. V.; Vytvytsky, I. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The movement of drilling mud through hydromonitor nozzles is investigated in the work. On the basis of the theory of destruction of rocks by a liquid stream the necessary values of pressure on hydromonitor nozzles of a drilling head for concrete values of mechanical properties of the drilled breed are found. The results of the performed analytical researches were used for modeling of processes of movement of a stream of washing liquid through hydromonitor nozzles of a bit with use of the Flow Simulation CAD / CAM package of the Solid Works system. During the simulation following parameters were investigated: the location of the nozzles at different distances from the axis of the bit and from the bottom of the well, pressure distribution at the bottom of the well at the exit of the flushing fluid from each nozzle and the velocity of the jet and the wall of the well, the vorticity of the jets on the bottom and the walls of the well. According to the results of research design of the hydromonitor unit of the drilling head was improved and new tests were carried out in industrial conditions.